How Does Group Cohesiveness Contribute to Student Productivity and Performance?: A PRISMA Systematic Review - Galuh Nadhita; Heru Mugiarso; Banun Sri Haksasi; Ayu Fadjri Agustiani (Indonesian Journal of Guidance and Counseling: Theory and Application, 2024)
Group cohesiveness has long been recognised as an important factor in enhancing individual performance in various social and educational contexts. This research aims to explore the role of group cohesiveness on improving student productivity and performance. The main focus of this research is to identify how factors such as trust, communication, and commonality of group goals contribute to group effectiveness in an educational context. This study present a literature review with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to synthesise the findings from various related studies that have been conducted previously. Critically selected articles were analysed to illustrate the internal and external mechanisms that review the role of group cohesiveness on students' academic productivity and performance. The findings of this study indicate that group cohesiveness has an important and explorative role on students' productivity and performance. The results of this literature synthesis are expected to provide a deeper understanding of how classroom management practices and educational interventions can utilise group cohesiveness to improve learning outcomes. This research provides valuable insights for educators, school administrators and researchers to develop more effective intervention strategies to improve group cohesiveness in classrooms and schools, with the ultimate goal of improving students' academic performance and overall learning experience. Kekompakan kelompok telah lama dikenal sebagai faktor penting dalam meningkatkan kinerja individu dalam berbagai konteks sosial dan pendidikan. Penelitian ini bertujuan untuk mengeksplorasi peran kekompakan kelompok terhadap peningkatan produktivitas dan kinerja siswa. Fokus utama penelitian ini adalah untuk mengidentifikasi bagaimana faktor-faktor seperti kepercayaan, komunikasi, dan kesamaan tujuan kelompok berkontribusi terhadap efektivitas kelompok dalam konteks pendidikan. Penelitian ini menyajikan tinjauan literatur dengan kerangka Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) untuk mensintesis temuan dari berbagai penelitian terkait yang telah dilakukan sebelumnya. Artikel-artikel yang dipilih secara kritis dianalisis untuk menggambarkan mekanisme internal dan eksternal yang meninjau peran kekompakan kelompok terhadap produktivitas dan kinerja akademik siswa. Temuan penelitian ini menunjukkan bahwa kekompakan kelompok mempunyai peran penting dan eksploratif terhadap produktivitas dan kinerja siswa. Hasil sintesis literatur ini diharapkan dapat memberikan pemahaman yang lebih mendalam tentang bagaimana praktik pengelolaan kelas dan intervensi pendidikan dapat memanfaatkan kekompakan kelompok untuk meningkatkan hasil pembelajaran. Penelitian ini memberikan wawasan berharga bagi para pendidik, administrator sekolah, dan peneliti untuk mengembangkan strategi intervensi yang lebih efektif guna meningkatkan kekompakan kelompok di ruang kelas dan sekolah, dengan tujuan akhir meningkatkan kinerja akademik siswa dan pengalaman belajar secara keseluruhan.